Algorithm of Hypertensive Urgency Management to Reduce Mass Accumulation During the Third Stage of Hajj Pilgrims' Health Examination: Case Report - Kusuma, Muhammad A’raaf Sirojan; Indradmojo, Christyaji (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 3 (2025): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2026)
The Hajj pilgrimage involves air travel to Saudi Arabia, which poses physiological risks such as hypobaric hypoxia due to decreased air pressure and oxygen saturation, particularly for elderly pilgrims with comorbidities like hypertension. This study evaluates the stage 3 health examination process at the Surabaya Hajj Dormitory to determine fitness to fly status, based on IATA guidelines that classify hypertension as a potential aviation safety risk. Hajj pilgrims experiencing hypertensive urgency are also unable to be sent to the holy land because they do not meet the requirements for hajj istita'ah. The discussion covered the mechanisms of hypoxia compensation that increase blood pressure, potentially leading to heart failure or stroke. Analysis of four cases of hypertensive urgency showed variations in management, such as rest, oral medication (amlodipine, captopril), or sublingual (ISDN), with a target blood pressure of <180/110 mmHg. Challenges include overcrowding, delays in mass gathering services, and a lack of special observation. Recommendations included creating a dedicated post for observing hypertensive urgency with manual/digital blood pressure monitors, treatment algorithms based on guidelines (captopril 12.5-25 mg, nifedipine 5-10 mg, ISDN 10 mg), strict monitoring to avoid hypotension, and effective communication with group officials for ongoing management. This effort aims to reduce flight risks and improve the efficiency of Hajj healthcare services.